Land Requirements for Freestall Dairy Facilities - Harner, Joseph P.; Smith, John F., 1962- (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Existing blueprints were used to estimate land requirements for new dairy facilities. The average land requirement for constructing a new dairy complex with freestall housing and a new parlor is 915 ft2 per lactating cow. Approximately 52% of the overall land space is used for dairy operations including a milk center, housing, transfer lanes, vehicle roads, a feed center, and a manure processing center. The remaining 48% is green space, areas between buildings or along driveways, and separation distance from main roads and neighboring property.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dairy; Dairy facilities; Land requirements